Developing Accounting Material Enriched with Balinese Cultural Values for Entrepreneurship Students - Premananda, Ni Putu Uttari; Wulandari, Putu Riska (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This research aimed to develop accounting learning materials based on Balinese cultural values, which can provide contextual learning and align with the characteristics of Indonesia, particularly Bali, in terms of its cultural values. The study employed the Research and Development method by ADDIE model design. In the analysis phase, the syllabus and lesson plan were thoroughly examined, involving educators and the existing teaching conditions. In the design phase, the product was transformed into an e-module with Balinese cultural values. During the development phase, validity tests and practicability tests were conducted to assess the usefulness and validity of the developed product. Validity tests conducted by 5 experts affirmed that the product was  categorized in the category of valid (layout, language, content). The outcome of  practicability testing also indicated product was categorized in good category, with specific scores of 817 points (88%) for content, 727 points (90%) for layout, and 514 points (89%) for language. This research is expected to provide high-quality teaching materials for educators in higher education, particularly for the accounting course.